Study on Fatigue Coefficient of Airline Pilots - Zhang, Peiwen; Zhao, Wenke; Shi, Lan; Wang, Yu; Sun, Hong; Sun, Zhen (Frontiers in Psychology, 2022)
In order to evaluate the fatigue status of pilots, this paper uses the Multidimensional Fatigue Inventory (MFI-16) to collect pilot fatigue related data, and tests the reliability and validity of the survey data by Cronbach’s α and exploratory factor analysis. It is found that the fatigue status is above mild fatigue, accounting for 67.7%. This paper uses multi factor analysis of variance and multiple linear regression for further characterize the impact of different flight types on pilots fatigue feeling from the perspective of different flight take-off and landing times and whether it involves plateau areas. It is found that the independent variables have different and positive effects on the dependent variables, and there is no multicollinearity problem. Through the actual test, its accuracy is improved by 15.4% compared with the original model, and has a good fatigue monitoring effect.